Hydrotropic oligomer-conjugated glycol chitosan as a carrier of paclitaxel: Synthesis, characterization, and in vivo biodistribution - Saravanakumar, G.; Min, Kyung Hyun; Min, Dong Sik; Kim, Ah Young; Lee, Chang-Moon; Cho, Yong Woo; Lee, Sang Cheon; Kim, Kwangmeyung; Jeong, Seo Young; Park, Kinam; Park, Jae Hyung; Kwon, Ick Chan (Journal of controlled release, 2009)
Development of successful formulations for poorly water-soluble drugs remains a longstanding critical and challenging issue in cancer therapy. As a potential drug carrier of paclitaxel, hydrotropic oligomer-glycol chitosan (HO-GC) was synthesized by chemical conjugation of the N,N-diethylnicotinamide-based oligomer, uniquely designed for enhancing the aqueous solubility of paclitaxel, to the backbone of glycol chitosan. Owing to its amphiphilicity, the conjugate formed self-assembled nanoparticles with a mean diameter of 313 ± 13 nm in a phosphate-buffered saline (PBS, pH 7.4 at 37 °C). HO-GC nanoparticles maintained their structure for up to 50 days in PBS. They could encapsulate a high quantity (20 wt.%) of paclitaxel (PTX) with a maximum drug-loading efficiency of 97%, due to the presence of hydrotropic inner cores. When HO-GC-PTX particles were exposed to the 0.1 M sodium salicylate solution in PBS (pH 7.4), PTX was released from nanoparticles in a sustained manner. From the cytotoxicity test, it was confirmed that HO-GC-PTX nanoparticles showed lower cytotoxicity than free PTX formulation in 50%/50% Cremophor EL/ethanol mixture. The optical imaging results indicated that near-infrared fluorescence dye (Cy5.5)-labeled HO-GC-PTX showed an excellent tumor specificity in SCC7 tumor-bearing mice, due to the enhanced permeation and retention effect. Overall, HO-GC-PTX nanoparticles might be a promising carrier for PTX delivery in cancer therapy. A hydrotropic oligomer-glycol chitosan (HO-GC) conjugate, with unique hydrotropic characteristics towards paclitaxel (PTX), was designed, synthesized, and evaluated as the drug carrier. Notably, HO-GC nanoparticles imbibed relatively high quantity of PTX compared to other polysaccharide-based carriers. In vivo studies showed enhanced tumor targeting ability of HO-GC nanoparticles.